Answer:
14
Step-by-step explanation:
note that (f - g) = f(x) - g(x)
f(x) - g(x) = 3x² + 1 - (1 - x) = 3x² + 1 - 1 + x = 3x² + x
To evaluate (f - g)(2) substitute x = 2 into f(x) - g(x)
(f - g)(2) = 3(2)² + 2 = (3 × 4) + 2 = 12 + 2 = 14
Answer:
3/16
Step-by-step explanation:
2^-4 = 1/2^4 = 1/16
Answer:4.5 x 2
Step-by-step explanation:
4.5 x 2 = 9
Hope it helps
Answer:
The answer to your question is letter D
Step-by-step explanation:
Formula
m∠E = ![\frac{1}{2} ( DGF - DF)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%28%20DGF%20-%20DF%29)
Data
m∠E = 48°
DGF = 228°
DF = x°
Substitution
48° = ![\frac{1}{2} ( 228° - x°)](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%28%20228%C2%B0%20-%20x%C2%B0%29)
Solution
2(48) = 228 - x°
96 = 228 - x°
96 - 228 = - x°
- 132 = - x°
x° = 132°